Betaine Attenuates Chronic Constriction Injury-Induced Neuropathic Pain in Rats by Inhibiting KIF17-Mediated Nociception - Tiwari V.; Hemalatha S. (My University, 2025)
Kinesin superfamily proteins transport a diverse range of cargo, including excitatory receptors to the dendrite and axon of a neuron via retrograde and anterograde fashions along microtubules, causing central sensitization and neuropathic pain. In this study, we have performed in silico molecular dynamics simulation to delineate the dynamic interaction of betaine with KIF17, a kinesin protein, known to be involved in neuropathic pain. The results from the molecular dynamics study suggest that the betaine-KIF17 complex is stabilized through hydrogen bonding, polar interactions, and water bridges. Findings from in vivo studies suggest a significant increase in pain hypersensitivity, oxido-nitrosative stress, and KIF17 overexpression in the sciatic nerve, dorsal root ganglion (DRG), and spinal cord of nerve-injured rats, which was significantly attenuated on treatment with betaine. Betaine treatment also restored the increased NR2B expressions and levels of proinflammatory cytokines and neuropeptides in the DRG and spinal cord of nerve-injured rats. Findings from the current study suggest that betaine attenuates neuropathic pain in rats by inhibiting KIF17-NR2B-mediated neuroinflammatory signaling. © 2022 American Chemical Society.